El papel de las mujeres como jefe de hogar y su incidencia en las desigualdades socioeconómicas de los hogares de la parroquia Arenillas, cantón Arenillas, 2014 - Cañarte Toledo, Valeria Andrea (2015)
The access limited to the opportunities that there have had the women of the parish Arenillas has caused that its hearths suffer of major inequality and consequently less socioeconomic conditions in comparison to the hearths headed by a male. In order to analyze these variables and propose strategies to improve the standard of living of households headed by women, It was conducted the research called: "The role of the women as chief of hearth and its incidence in the socioeconomic inequality of the hearths of the parish Arenillas, Canton Arenillas, 2014”. The general target was to Characterize the chiefs of feminine hearth, using an analytical study, with the purpose to determine their impact on the socioeconomic conditions of households in the parish Arenillas, canton Arenillas, year 2014, to generate a source of information for the governmental agency that will serve as a tool in the development of future strategies for the reduction of social inequities. For which, was used the method of scientific research, especially the following expressions of this method were used: deductive method, inductive method, and analytical method. In addition were used the bibliographic technical, and survey The most important result derived from this work demonstrate that the housing conditions, access to basic services and the information and communication technologies, are better in the households headed by a male; additionally the levels of poverty and inequality of the per capita income are higher in homes that have as chief of hearth a woman. In conclusion gender of chief of hearth affects the socioeconomic conditions of households, that is, households headed by women are in less favorable position. Keywords: Socioeconomic inequality, poverty, hearth chiefs.